Genetics of stroke in Qatar: Current situation and future opportunities - Khan, Fahmi Yousef (Eastern Journal of Medical Sciences, 2021)
Recent studies have shown that genetic factors may play an important role in the pathogenesis of stroke, as known modifiable and non-modifiable risk factors may account for only 50% of the risk of stroke. Evidence for a genetic basis can be elucidated from twin studies, family history studies, and animal models. Qatar is currently leading the stroke initiative in the Gulf region with a view toward joining the genomic revolution. In collaboration with a team of scientists from Royal Holloway College, University of London, and Imperial College London, we took the initial step in this field by establishing the first biorepository of deoxyribonucleic acid in stroke in the Middle East. In this review, we describe our current situation in the field of stroke genetics with an exploration of future opportunities.